Effectiveness of body roundness index for the prediction of nonalcoholic fatty liver disease: a systematic review and meta-analysis - Shaghayegh Khanmohammadi; Parisa Fallahtafti; Amirhossein Habibzadeh; Ali Ezzatollahi Tanha; Amir Ali Alamdari; Parsa Fallahtafti; Mohammad Shafi Kuchay (Lipids in Health and Disease)
Abstract Background Several anthropometric indices, such as body mass index and waist circumference, have been used as clinical screening tools for the prediction of nonalcoholic fatty liver disease (NAFLD). To further refine these clinical tools for NAFLD, the body roundness index (BRI) has recently been evaluated. In this systematic review and meta-analysis, the objective was to evaluate the relationship and predictive capability of the BRI in identifying NAFLD. Methods A comprehensive search was conducted in PubMed, Embase, Web of Science, and Scopus up to December 31, 2024. Eligibility criteria included observational studies on adults (≥ 18 years old) with measured BRI and its association with NAFLD. The Joanna Briggs Institute tool was used for risk of bias assessment. Meta-analyses used random-effects models to pool data on mean difference, odds ratio, sensitivity, specificity, and the area under the curve (AUC), with heterogeneity and publication bias assessed. Results Ten studies involving 59,466 participants were included. The pooled mean difference in BRI between the NAFLD and non-NAFLD groups was 1.73 (95% confidence interval [CI]: 1.31–2.15). The pooled sensitivity and specificity of BRI for diagnosing NAFLD were 0.806 and 0.692, respectively. The pooled AUC for BRI was 0.803 (95% CI: 0.775–0.830), indicating good diagnostic accuracy. Unlike subgroup analysis by country, subgroup analysis by sex showed no significant differences. Higher BRI values were associated with increased odds of NAFLD (pooled OR = 2.87, 95% CI: 1.39; 5.96). Studies provided mixed results on the predictive ability of BRI compared to other indices like body mass index, mostly favoring BRI over conventional indices. Conclusion BRI demonstrates a good diagnostic performance for NAFLD, suggesting it may be a valuable clinical tool for NAFLD assessment. Further research is necessary to validate these findings and strengthen the evidence base.